Industrial waste lignin as an antifouling coating for the treatment of oily wastewater: Creating wealth from waste. (20th May 2020) - Shamaei, Laleh; Khorshidi, Behnam; Islam, Muhammad Amirul; Sadrzadeh, Mohtada
Abstract: Treatment of oily wastewater is of paramount importance to prevent unbearable water pollution caused by large discharge volume from industrial and household activities. Membrane technology is an effective oily wastewater treatment technology. However, it suffers from fouling if the membrane element is not modified to possess anti-oil-fouling propensity. Here, we converted an agro-industrial waste into an asset by coating hydrophilic sulfonated kraft lignin on polyethersulfone (PES) membrane using layer-by-layer (LbL) assembly. The polyelectrolytes used in the LbL process were lignin as a polyanion and poly (diallyldimethylammonium chloride) (pDAC) as a polycation. The effects of polyelectrolyte concentration and the number of coating bilayers were examined to fabricate a membrane with an enhanced anti-fouling propensity and minimal loss in permeation performance. The membrane with the highest anti-fouling performance was obtained by coating 3 pDAC/lignin bilayers with 2 wt% concentration of the individual polyelectrolyte solution. This membrane demonstrated a low flux decline of 23.1%, and a high flux recovery ratio of 93.8% when was utilized for the filtration of the n-hexadecane-in-water emulsion as synthetic oily wastewater. The pristine PES membrane showed a flux decline of 44.2%, and the flux recovery ratio of 75.9% under similar test conditions. The improvement in anti-fouling properties of the LbL-assembled membrane was achieved due to its higher underwater oleophobicity (22.6° ± 0.5°) as compared to the pristine PES membrane (71.1° ± 0.7°). The present study opens up a new paradigm to develop anti-fouling membranes by using hydrophilic industrial waste lignin in LbL surface modification of conventional polymeric membranes for oily wastewater treatment. Graphical abstract: Image 109595 Highlights: An industrial waste was converted to an asset for oily wastewater treatment. Lignin was used for surface hydrophilization of membrane via layer-by-layer assembly. Lignin-modified membranes showed remarkable improvement in antifouling properties. Underwater surface wettability of lignin-modified membranes improved significantly. The best membrane showed low flux decline (23%) and high flux recovery ratio (94%).